TEOREMA WEYL UNTUK OPERATOR HYPONORMAL - Gunawan Gunawan (Unisda Journal of Mathematics and Computer Science (UJMC), 2017)
This paper aims at describing the natures of Hyponormal operator to secure the existence of Weyl’s theorem. The discussion on Weyl’s theorem requires definitions of compact, Fredhlom, and Weyl’s operator. In addition, samples and natures of compact and Fredhlom operator in Hilbert space will also be observed.